The EU's Botched Geopolitical Approach to External Energy Policy: The Case of the Southern Gas Corridor. Issue 1 (1st January 2019) - Siddi, Marco
ABSTRACT: This article argues that the European Union (EU) has pursued a geopolitical approach to its external energy policy in the Caspian region, with the aim of importing gas via routes that bypass Russia. This approach treats energy as a strategic good that governments need to secure through political, diplomatic and economic involvement in energy trade. The geopolitical approach differs from the traditional EU stance to energy policy, which focuses on market liberalization, competition, and climate targets. Through an analysis of key policy documents and statements of top EU officials in charge of external energy policy, the article shows that the Southern Gas Corridor (SGC) exemplifies a geopolitical approach to energy. In a second step, it highlights how the geopolitical logic that permeates the SGC has underplayed the important economic, technical and security challenges hindering the project. These challenges are compounded by Russia's response, which aims at strengthening competition to SGC gas through new export pipelines (Turkish Stream). Finally, the article argues that, due to the multiple challenges faced by the geopolitical approach, the EU is more likely to achieve energy security through its traditional market liberal approach. As a large, integrated and well-regulated market, the EU can acquire sufficient and affordable energy resources by encouraging competition among external suppliers and by relying on the existing, underutilized import infrastructure. Furthermore, the implementation of the EU's climate agenda makes long-term projects for the import of fossil fuels such as the SGC largely redundant.